PENGARUH KOMITMEN ORGANISASI, ORIENTASI ETIKA IDEALISME DAN ORIENTASI ETIKA RETALIVISME TERHADAP MINAT MELAKUKAN WHISTLEBLOWING (Studi Empiris Pada PT.Telkomsel Provinsi Riau) - Fany Audia Irjanti; Raja Adri Satriawan Putra; Arumega Zarefar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The aim of this study is to examine the influence of organizational commitment, Ethical Orientation Idealism and Ethical Orientation Relativism To Whistleblowing Intention. This study was conducted at all branches PT.Telkomsel in Riau Province. The sampling method that used in this study is purposive sampling. Collecting data of this study using a questionnaire submitted to 150 employees working in all branches of PT.Telkomsel riau province. From questionnaires distributed, 76 questionnaires can be completed and can be processed. Data collected were analyzed with Partial Least Square (PLS). The results of hypotesis testing conclude that: first, organizational commitment has positif influence toward whistleblowing intention. Second, Ethical Orientation Idealism has positif influence toward whistleblowing intention Third, Ethical Orientation Relativism has negative influence toward whistleblowing intention.Keywords: Organizational Commitment, Ethical Orientation Idealism, Ethical Orientation Relativism and Whistleblowing intention